Assessment of Oral Hygiene and Gingival Health Condition and their Relationship with Some Salivary Variables among Boxers - Majhool, Haneen Obied; Qasim, Alhan Ahmed (AL-Kindy College Medical Journal, 2024)
Background: Background oral hygiene means the degree of cleanliness of the oral cavity. Good oral hygiene is necessary to prevent common oral diseases. Objectives: to evaluate the relation of some salivary variables to oral hygiene and gingival health conditions among Iraqi boxers. Subjects and Methods: There was a cross-sectional comparative study. The total sample consisted of 80 males, including 40 male boxing players with weights ranging from (46-60 kg) attending different sports clubs for boxers in Baghdad (study group). And 40 male school students from some schools in Baghdad (comparative groups), ages ranging from (15-16) years old. This study was conducted from January-2022 to the end of May -2022. The unstimulated salivary analysis included samples collected flow rate, pH, and Minerals (calcium and phosphate) and salivary immunoglobulin A. After that, the clinical Assessment of gingival disease, calculus and plaque were assessed. Results: The results demonstrate that plaque and calculus are higher in the study group than in the control with a significant difference in plaque index and no significant difference in calculus. Concerning correlations, a weak negative significant correlation between flow rate and plaque index in control weakens the negative significance between Gingival index and PH, while other results are insignificant. Also, Findings show a weak negative significant correlation between plaque index and salivary IgA and a weak negative significant correlation between Gingival index and calcium and phosphorous in control. Conclusions: In conclusion, boxer players were associated with high gingival index, calculus and plaque index compared to control groups.